Coagulation management and transfusion in massive postpartum hemorrhage. Issue 3 (22nd June 2023) - Massoth, Christina; Wenk, Manuel; Meybohm, Patrick; Kranke, Peter
Abstract : Purpose of Review: Excessive bleeding during and following childbirth remains one of the leading causes of maternal mortality. Recent findings: Current guidelines differ in definitions and recommendations on managing transfusion and hemostasis in massive postpartum hemorrhage (PPH). Insights gained from trauma-induced coagulopathy are not directly transferable to the obstetric population due to gestational alterations and a differing pathophysiology. Summary: Factor deficiency is uncommon at the beginning of most etiologies of PPH but will eventually develop from consumption and depletion in the absence of bleeding control. The sensitivity of point-of-care tests for fibrinolysis is too low and may delay treatment, therefore tranexamic acid should be started early at diagnosis even without signs for hyperfibrinolysis. Transfusion management may be initiated empirically, but is best to be guided by laboratory and viscoelastic assay results as soon as possible. Hypofibrinogenemia is well detected by point-of-care tests, thus substitution may be tailored to individual needs, while reliable thresholds for fresh frozen plasma (FFP) and specific components are yet to be defined. In case of factor deficiency, prothrombin complex concentrate or lyophilized plasma allow for a more rapid restoration of coagulation than FFP. If bleeding and hemostasis are under control, a timely anticoagulation may be necessary.